C1q/TNF‐related protein‐1 functions to protect against acute ischemic injury in the heart. Issue 3 (17th November 2015) - Yuasa, Daisuke; Ohashi, Koji; Shibata, Rei; Mizutani, Naoki; Kataoka, Yoshiyuki; Kambara, Takahiro; Uemura, Yusuke; Matsuo, Kazuhiro; Kanemura, Noriyoshi; Hayakawa, Satoko; Hiramatsu‐Ito, Mizuho; Ito, Masanori; et al.
Abstract : Obesity is associated with an increased risk of cardiovascular disease. C1q/TNF‐related protein (CTRP)‐1 is a poorly characterized adipokine that is up‐regulated in association with ischemic heart disease. We investigated the role of CTRP1 in myocardial ischemia injury. CTRP1‐knockout mice showed increased myocardial infarct size, cardiomyocyte apoptosis, and proinflammatory gene expression after I/R compared with wild‐type (WT) mice. In contrast, systemic delivery of CTRP1 attenuated myocardial damage after I/R in WT mice. Treatment of cardiomyocytes with CTRP1 led to reduction of hypoxia‐reoxygenation‐induced apoptosis and lipopolysaccharide‐stimulated expression of proinflammatory cytokines, which was reversed by inhibition of sphingosine‐1‐phosphate (S1P) signaling. Treatment of cardiomyocytes with CTRP1 also resulted in the increased production of cAMP, which was blocked by suppression of S1P signaling. The antiapoptotic and anti‐inflammatory actions of CTRP1 were cancelled by inhibition of adenylyl cyclase or knockdown of adiponectin receptor 1. Furthermore, blockade of S1P signaling reversed CTRP1‐mediated inhibition of myocardial infarct size, apoptosis, and inflammation after I/R in vivo. These data indicate that CTRP1 protects against myocardial ischemic injury by reducing apoptosis and inflammatory response through activation of the S1P/cAMP signaling pathways in cardiomyocytes, suggesting that CTRP1 plays a crucial role in the pathogenesis of ischemic heart disease.—Yuasa, D., Ohashi, K., Shibata, R., Mizutani, N., Kataoka, Y., Kambara, T., Uemura, Y., Matsuo, K., Kanemura, N., Hayakawa, S., Hiramatsu‐Ito, M., Ito, M., Ogawa, H., Murate, T., Murohara, T., Ouchi, N., C1q/TNF‐related protein‐1 functions to protect against acute ischemic injury in the heart. FASEB J. 30, 1065–1075 (2016). www.fasebj.org